Formal Synthesis of (±)‐Morphine. Issue 6 (18th March 2013) - Li, Jing; Liu, Guo‐Liang; Zhao, Xian‐He; Du, Ji‐Yuan; Qu, Hu; Chu, Wen‐Dao; Ding, Ming; Jin, Cong‐Yang; Wei, Meng‐Xue; Fan, Chun‐An
<x xml:space="preserve">Abstract</x> The pain ends here: A novel synthetic strategy for the construction of (±)‐morphine rings B and E was developed, in which SmI2‐promoted reductive coupling/desulfurization and tandem alcoholysis/oxa‐Michael addition featured as the key steps for the assembly of the C9C14 and C5O bonds, respectively. Asymmetric tandem alcoholysis/oxa‐Michael addition was also feasible for the enantiocontrolled synthesis of morphine.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>